Perspektif Hak Asasi Manusia terhadap Tindakan Kekerasan Aparat Kepolisian dalam Kasus Pelindasan Pengendara Ojek Online di Indonesia - Ridwansyah Ridwansyah; Insan Tajali Nur; Nia Lestina; Sabam M. Monang Bakara; Sintong Sihite; Sitompul Charles Marolop (Pusat Riset dan Inovasi Nasional, 2024)
The right to life is a non-derogable human right and constitutes a fundamental obligation of the state in all public policies, including public security. However, in the practice of handling mass demonstrations, the protection of the right to life often conflicts with a security paradigm that prioritizes stability and public order. This study aims to analyze the failure of state security policies in protecting the right to life of civilians by using the death of Affan Kurniawan during a mass protest operation as an entry point for analysis. This research employs a normative juridical approach through the examination of legislation, police regulations, and human rights literature. The findings indicate a significant gap between legal norms that guarantee the protection of the right to life and their implementation in crowd control practices. Civilian deaths in this context cannot be understood merely as individual incidents, but rather as preventable deaths resulting from the state’s failure to manage the risks associated with the use of force. The study highlights the need for a shift in security policy from a state-centered security approach toward a human security paradigm that places the protection of human life and dignity at the core of public security governance.